Análisis del cumplimiento tributarío correspondiente al período fiscal 2008, de una empresa cuya actividad es la transportación de combustible y derivados de petróleo, por vía marítima y cabotaje - Bayas Egas, Alex Andrés (2009)
Our purpose in the project of thesis is "to analyze the taxpayer's compliance corresponding to the fiscal period 2008 of a dedicated company of service to the marine transportation of having derived of petroleum and coastal traffic" for we base ourselves to it on audit tests with the purpose of reconciling the countable bills with the declarations introduced to the Agent SRI, evaluating its razonabilidad and determining possible contingencies. For the revision took into account the formal and legal obligations of the company we apply laws, norms, regulations, codes and among other documents emitted by the State and demanded for the organizations. As result, we elaborated a tributary audit report with every formalities of the law directed to the shareholders and the meeting of directory where an opinion was expressed with respect to the taxpayer's compliance of the Company, to finish we analyzed and to make up one’s mind the conclusions and recommendations to take opportune corrections avoiding future inconveniences with the entity regulator.